Effects of skills, motivation, and personality traits on the competency of masons. (2017) - Choudhry, Rafiq Muhammad; Zafar, Bilal
Incompetency of masons is a problem because they execute many construction activities. This imparts the need to identify factors that affect the competency of masons on construction sites. Factors related to motivation, skills and personality traits are identified. A questionnaire instrument consisting of 15 factors related to the three categories was forwarded to masons on construction projects. Responses collected on a five-point Likert scale were analysed for relative importance index (RII), which was used as the basis for ranking the factors. 'Resistance to change', 'lack of appreciation', and 'lack of formal training' were identified as the first, second, and third most important factors affecting the competency of masons on construction projects. The impact of the category of motivation was found to be the highest on the competency of masons, followed by skills, and personality traits. These findings may be utilised as an assessment tool for determining the competency of masons and identifying areas that need improvements.